Extra Judicial Killing Dalam Perspektif Hukum Positif dan Hukum Pidana Islam - Eva Wulandari; Evi Ariyani (Jurnal Al-Hakim: Jurnal Ilmiah Mahasiswa, Studi Syariah, Hukum dan Filantropi, 2022)
This study aims to find out Extra Judicial Killing in the perspective of Positive Law and Islamic Criminal Law.  Extra Judicial Killing is a crime that until now has become a byword among the public which can be interpreted as an act of any kind that causes a person to die without going through a legal process and trial, and is carried out by State Apparatus.  This is not in accordance with the Indonesian criminal justice system, especially in the investigation process or in other words not paying attention to the principle of fair trial.  Extra Judicial Killing in the perspective of Positive Law has fulfilled the elements of a material offense. Articles that fulfill are primary Article 338 of the Juncto Criminal Code Article 55 paragraph (1) of the 1st Criminal Code and a subsidiary Article 351 paragraph (3) of the Juncto Criminal Code Article 55 paragraph (1) of the 1st Criminal Code and are acts of any form causing a person to die without going through a process.  Laws and courts are legally carried out by State Apparatus. Meanwhile, from the perspective of Islamic Criminal Law, Extra Judicial Killing is included in the Jarimah Qatlu al-'amd. Abstrak Penelitian ini bertujuan untuk dapat mengetahui Extra Judicial Killing dalam perspektif Hukum Positif dan Hukum Pidana Islam. Extra Judicial Killing merupakan kejahatan yang sampai detik ini menjadi buah bibir di kalangan masyarakat yang dapat diartikan suatu tindakan apapun bentuknya yang menyebabkan seorang mati tanpa melalui proses hukum dan pengadilan yang sah, serta dilakukan oleh Aparat Negara. Hal ini tidak sesuai dengan sistem peradilan pidana Indonesia, terutama dalam proses penyelidikan atau dengan kata lain tidak memperhatikan prinsip fair trial. Extra Judicial Killing dalam perspektif Hukum Positif sudah memenuhi unsur-unsur delik materil. Pasal yang memenuhi yaitu Primair Pasal 338 KUHP Juncto Pasal 55 ayat (1) ke-1 KUHP dan subsidair Pasal 351 ayat (3) KUHP Juncto Pasal 55 ayat (1) ke-1 KUHP dan merupakan tindakan apapun bentuknya menyebabkan seorang mati tanpa melalui proses hukum dan pengadilan secara sah yang dilakukan oleh Aparat Negara. Sedangkan dalam perspektif Hukum Pidana Islam, Extra Judicial Killing termasuk dalam jarimah Qatlu al-‘amd.